Geophysical evidence for submarine methane seepage on the Western slope of Okinawa Trough - Luo, Di; Cai, Feng; Li, Qing; Yan, Guijing; Sun, Yunbao; Li, Ang; Dong, Gang (Frontiers in Earth Science, 2022)
Identifying seafloor methane seepage efficiently has significant implications in assessing environmental impact, reducing the uncertainty of top seal integrity, understanding the petroleum system, and mitigating the drilling hazards due to shallow gas influx. Geophysical dataset from the western slope of Okinawa Trough, including high-resolution seismic, sub-bottom profiles, and bathymetry, revealed numerous methane seepage-related features, such as seismic chimneys, pockmarks, submarine mounds, and amplitude anomalies including bright spots and enhanced reflections. Pore water geochemistry analyses suggest an extremely high methane seepage flux and active methane anaerobic oxidation processes in the study area. Chaotic or blanking reflections have been observed within seismic chimneys, and several enhanced reflections or bright spots are sometimes observed within or immediately adjacent to them. Pockmarks and domes are often connected to seismic chimneys, indicating that fluid migration plays an important role in their formation. According to the relationship with faults, methane seepages have been sorted into two kinds. Type A is associated with faults while Type B does not exhibit a clear relationship with faults. Several flares above domes or pockmarks indicate that fluids are actively migrating upward.